Radiation reaction for spinning bodies in effective field theory. I. Spin-orbit effects - Maia, Natalia T. [UNESP]; Galley, Chad R.; Leibovich, Adam K.; Porto, Rafael A. [UNESP] (Amer Physical Soc, 2017)
We compute the leading post-Newtonian (PN) contributions at linear order in the spin to the radiationreaction acceleration and spin evolution for binary systems, which enter at fourth PN order. The calculation is carried out, from first principles, using the effective field theory framework for spinning compact objects, in both the Newton-Wigner and covariant spin supplementary conditions. A nontrivial consistency check is performed on our results by showing that the energy loss induced by the resulting radiation-reaction force is equivalent to the total emitted power in the far zone, up to so-called Schott terms. We also find that, at this order, the radiation reaction has no net effect on the evolution of the spins. The spin-spin contributions to radiation reaction are reported in a companion paper.